Oral management of patients with cancer - Claudia Patricia López-Silva; Mathew Albert Wei-Ting; Pritam Daniel Sundaresan; Gelsomina Borromeo (Universidad de Antioquia, 2019)
The oral management of individuals affected by medical conditions, including those with a current cancer diagnosis, is often complex and as such should be provided by either experienced dentists or dental specialists (e.g. Special Needs Dentists) with adequate training and experience. Patients with cancer need early dental intervention as the cancer itself or its therapy may place them at increased risk of systemic and oral complications. In Colombia, Special Needs Dentistry (SND) has not been formally recognized as a specialty and does not form part of the current dental curricula suggesting a paucity of suitably qualified dentists to provide complex oral care for oncology patients. While it is accepted that general dentists will provide the bulk of care to these individuals, their knowledge base is unclear. This paper aims to improve the knowledge base around complex SND by addressing the oral complications faced by this patient cohort and how to prioritize treatment, together with proposing a simple protocol to streamline coordination of care between the dental, allied health and medical teams, that is, through a multidisciplinary approach. It is important to acknowledge that dentists have a role at all three levels of the multidisciplinary management of cancer.